A New Model to Perform Electrophysiological Studies in the Early Embryonic Mouse Heart - Anna Kornblum; Frank Pillekamp; Matthias Matzkies; Bernd Fleischmann; Hendrik Bonnemeier; Heribert Schunkert; Konrad Brockmeier; Jürgen Hescheler; Michael Reppel (Cellular Physiology and Biochemistry, 2013)
Background: The first electrocardiograms (ECGs) have been recorded with a capillary electrometer in the late 19th century by John Burdon Sanderson and Augustus Waller. In 1903 Willem Einthoven used the much more sensitive string galvanometer and was awarded Nobel Price in Medicine for this discovery. Though the physical principles of that era are still in use, there have been many advances but also challenges in cardiac electrophysiology over the last decades. One challenge is to record electrocardiograms of rather small animals such as mice and even smaller organisms such as their embryos. As mice belong to the most routinely used laboratory animals it is important to better understand their physiology and specific diseases. We therefore aimed to study whether it is feasible to measure electrical activities of embryonic mouse hearts. Methods and Results: For our studies we used substrate-integrated Microelectrode Arrays combined with newly developed stimulation electrodes to perform electrophysiological studies in these hearts. The system enabled us to perform ECG-like recordings with atrio-ventricular (anterograde) and ventriculo-atrial (retrograde) stimulation. The functional separation of atria and ventricles, indicated by a stable atrio-ventricular conduction time, occurred clearly earlier than the morphological separation. Electrical stimulation induced a reversible prolongation of the anterograde and retrograde conduction up to atrio-ventricular conduction blocks at higher frequencies. Conclusion: These results yield new insight into functional aspects of murine cardiac development, and may help as a new diagnostic tool to uncover the functional and electrophysiological background of embryonic cardiac phenotypes of genetically altered mice.